Anisotropic mechanical properties of coal in a water-immersed pillar dam: Insights from acoustic emission characterization - Ziwan Sun; Ru Zhang; Li Ren; Xiaoling Liu; Zhaopeng Zhang; Ersheng Zha; Xingyu Yang; Zhaohui Liu; Zetian Zhang (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
Safe operation of underground reservoirs in coal mines is crucial for the coordinated exploitation of coal and water resources in western China. Mine water infiltration significantly influences the stability of the coal pillar. Therefore, laboratory tests were systematically carried out on coal from the Daliuta Coal Mine in Northwest China. Samples were taken in the vertical and parallel bedding directions and soaked for 0 d, 2 d, 4 d, or 16 d. In this study, atomic absorption spectroscopy (AAS), X-ray diffraction (XRD), and scanning electron microscopy (SEM) were used to analyze the variations in the water absorption characteristics and corresponding internal structure of the coal. Uniaxial compression tests and synchronous acoustic emission (AE) monitoring revealed the sample failure process and mechanical properties of the samples. Finally, the time- and frequency-domain characteristics of the AE signal were comprehensively analyzed using fractal dimension, fast Fourier transform, and cluster analysis. The strength and elastic modulus demonstrate significant anisotropy with different bedding planes and reveal the existence of the optimum water content. Specifically, the sample strength increases after 2 d of immersion, with increments of 23.3% and 0.6% for the vertical and parallel bedding samples, and decreases after 16 d of immersion, with decreases of 29% and 45% for the vertical and parallel samples, respectively. Additionally, shear cracks account for over 60% during the damage development of the samples. The proportion of tensile cracks is higher for samples with longer immersion times and parallel bedding planes. This research provides a theoretical basis for stability evaluation and protection of coal pillars in underground reservoirs using the AE technique.